1997
DOI: 10.3168/jds.s0022-0302(97)75937-x
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Rates Per Artificial Insemination for Cows and Heifers Inseminated at a Synchronized Ovulation or Synchronized Estrus

Abstract: Two synchronization protocols were tested for lactating dairy cows and heifers. Nulliparous dairy heifers (13 to 23 mo; n = 155) and primiparous and multiparous dairy cows (60 to 289 d postpartum; n = 310) were assigned randomly to two treatments. Controls received 25 mg of PGF2 alpha and were artificially inseminated according to the a.m.-p.m. rule following detected estrus. All controls that were not detected in estrus were injected with 25 mg of PGF2 alpha at 14-d intervals until artificial insemination (AI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
248
4
33

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 398 publications
(295 citation statements)
references
References 14 publications
10
248
4
33
Order By: Relevance
“…However, the reproductive management advantage of the OVS program is that the insemination rate is higher. That reduces the mean days to first AI and days open and accelerated the rate of accumulated pregnancies [6,8,31]. In the current study, pregnancy rates either to the first or overall up to the fourth AI for primiparous and multiparous cows were similar.…”
Section: Ma Alnimersupporting
confidence: 54%
See 1 more Smart Citation
“…However, the reproductive management advantage of the OVS program is that the insemination rate is higher. That reduces the mean days to first AI and days open and accelerated the rate of accumulated pregnancies [6,8,31]. In the current study, pregnancy rates either to the first or overall up to the fourth AI for primiparous and multiparous cows were similar.…”
Section: Ma Alnimersupporting
confidence: 54%
“…Therefore, development of treatment programs that can effectively induce oestrus and ovulation in cows can have a major effect on herd reproductive performance. The Ovsynch program was developed allowing cows to be inseminated without the need for oestrus detection and improving reproductive performance during the early postparum period (around 50 d) with no labour investment for detecting oestrous [6][7][8][9]. Such a protocol consists of an injection of GnRH agonist given at random stages of the oestrous cycle followed, 7 d later by an injection of PGF 2α .…”
Section: Introductionmentioning
confidence: 99%
“…If a second injection of GnRH agonist is administered 36 to 48 h following PGF2a administration the ovulation is synchronized (3)(4)(5) and timed AI 16 to 24 h after the second dose of GnRH results in pregnancy rates similar to those observed in cows bred during normal estrus (4-7). Pursley et al (3) reported that pregnancy rates after timed AI were similar to those for cows bred 12 h after estrus detection (37.8 vs 38.9%). On the other hand, Roy and Twagiramungu (8), waiting only 6 days between the first GnRH injection and PGF2a administration, observed a high pregnancy rate (62.2%) in fixed-time AI beef heifers.…”
Section: Introductionmentioning
confidence: 96%
“…The administration of a second dose of GnRH 24 to 48 h after PGF2a causes a more precise synchronization of ovulation in both Bos taurus (7,32) and Bos indicus cows (33) and permits timed artificial insemination (3,5,32,34,35). Pursley et al (7) reported that all Holstein cows and 75% of the heifers ovulated within a period of 24 to 32 h after the second GnRH administration.…”
Section: Gpe-d6mentioning
confidence: 99%
See 1 more Smart Citation